The Principal Leadership in Indonesian Islamic School: The Strategy in Shaping the Academic Professionalism - Muli Umiaty Noer (Eduvest - Journal of Universal Studies, 2023)
An overview of the current situation of Indonesian Islamic schools may be viewed by examining the areas of management and educational assessment, as well as the schools' amenities and facilities, content, and procedure, as well as the competency of its graduates, teachers, and other educational staff. It has recently come to light that not all Islamic schools in Indonesia can adhere to these standards. This study aims to highlight how principals of Indonesian Islamic Schools promote the academic professionalism of teachers and other educational staff members. In the context of the study of Islamic leadership, it incorporates the idea that the essential leadership talent is instructional leadership. It is associated with the core skillsets of assessment, unity of purpose, diversity, reflection, professional development, curriculum and instruction, instructional leadership, visionary leadership, learning community, organizational management, collaboration, and professionalism. This qualitative research uses a descriptive case study approach to provide a detailed description of the phenomenon under study. Using a purposive sampling technique, data collection involved representatives from public and private Madrasah Aliyah (MA) institutions in Parepare, Indonesia. Our study found the core understanding of academic professionalism emphasizes professional development, social service, competence, and responsibility, requiring the support of a proper institutional outcome plan. It provides evidence that the leadership style of principals influences the academic professionalism of teachers and educational staff, directly contributing to school quality. The excellence of the program and alumni reflects the effectiveness of the leadership of the madrasah principal.